A Genre-Based Diagnostic Classroom Assessment of EFL Students’ Reading Comprehension - Irwan, Dedi (JET ADI BUANA, 2026)
Reading assessments in EFL classrooms frequently produce a single aggregate score that obscures the underlying sources of students’ comprehension difficulties. This study advances a genre-based diagnostic classroom assessment designed to reveal how reading performance varies across text types and to identify the specific cognitive and discourse-level processes requiring instructional attention. Grounded in Systemic Functional Linguistics (SFL) and genre theory, the framework treats genre as the analytical unit, examining how staged organization and linguistic realization shape comprehension outcomes. A 20-item multiple-choice assessment was administered to 15 second-semester EFL students, with items systematically mapped to five reading sub-skills: identifying main ideas, locating supporting details, tracking references, making inferences, and interpreting vocabulary in context. Descriptive statistics were integrated with genre-sensitive diagnostic interpretation. Results indicate systematic variation across genres: students performed more successfully on descriptive and narrative texts (70%) than on recount and procedure texts (60%). Sub-skill analysis further revealed a marked imbalance between literal comprehension (main ideas, details) and discourse-level integration (reference resolution, inferencing, contextual vocabulary), with gaps exceeding 25 percentage points. These findings demonstrate that reading difficulty is structurally patterned rather than uniform, intensifying when texts require chronological sequencing, logical progression, and cohesive tracking. By disaggregating performance according to genre and sub-skill, the proposed framework exposes diagnostic patterns that remain concealed in conventional aggregate scoring. The study reframes genre not only as a pedagogical construct but as a diagnostic variable capable of structuring classroom reading assessment. Pedagogically, the results underscore the need for explicit instruction in genre staging, cohesive devices, and inferential reasoning, particularly in structurally demanding genres such as recount and procedure.